Covid 19 dan Harga Saham Perbankan di Indonesia - Hana Tamara Putri (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2020)
This study examines whether there are differences in the prices of Top Ten shares of the Banking Company with the largest assets in Indonesia in three periods, namely the share price before Indonesia contracted Covid 19, the share price at the time of the announcement of the first case of Covid 19 in Indonesia and the Post-3 Month Share Price announcement of the Covid 19 case in Indonesia. Processed by means of the Paired Sample T test analysis results show that during the study period there were significant differences between the stock prices in the three periods.